Cutibacterium acnes strains associated with bone prosthesis infections cannot evade the host immune system - Thoraval, Léa; Tang-Fichaux, Min; Guillaume, Christine; Varin-Simon, Jennifer; Dumortier, Claire; Sergheraert, Johan; Lamret, Fabien; Bonhomme, Mélanie; Laurent, Frédéric; Josse, Jérôme; Gangloff, Sophie C.; Mongaret, Céline; et al. (Frontiers in Immunology, 2024)
IntroductionCutibacterium acnes is a commensal skin bacterium that is involved in bone prosthesis infections (BPIs) and presents low-grade clinical symptoms. C. acnes has been thought to escape the immune system at bone sites.Material and methodsOur study was carried out on a laboratory strain and two BPI-related clinical strains, one of which surprisingly induced clinical symptoms of inflammation in the patient. We investigated the ability of these C. acnes strains to trigger in vitro human primary neutrophils (PMN) response through inflammatory mediators measurements (antibody arrays, ELISA, RT-qPCR, zymography) and activation status assessment (flow cytometry), and to induce in vivo PMN recruitment from the bloodstream in mice air-pouch model. PMN-mediated inflammation was also studied in an original in vitro model mimetic of an infected bone site that combine titanium alloy, human primary osteoblasts, human primary neutrophils and C. acnes strains.ResultsWe demonstrated for the first time that both C. acnes planktonic and biofilm cultures, triggered an effective immune response by neutrophils in vitro and their recruitment in vivo. This host response was enhanced when using a strain from a patient with inflammatory signs. In an original infected prosthesis mimetic model, osteoblasts and neutrophils were able to detect C. acnes, but their response to the clinical C. acnes inflammatory strain decreased.ConclusionThis work provides the first evidence showing that the immune cell response to pathogenic C. acnes may be tuned by nonimmune cells at the infected site, such as osteoblasts, which may promote bacterial persistence.